Intramucosal-arterial PCO2 gap fails to reflect intestinal dysoxia in hypoxic hypoxia - Dubin, Arnaldo (2002)
Introduction. An elevation in intramucosal-arterial PCO2 gradient (ΔPCO2) could be determined either by tissue hypoxia or by reduced blood flow. Our hypothesis was that in hypoxic hypoxia with preserved blood flow, ΔPCO2 should not be altered. Methods. In 17 anesthetized and mechanically ventilated sheep, oxygen delivery was reduced by decreasing flow (ischemic hypoxia, IH) or arterial oxygen saturation (hypoxic hypoxia, HH), or no intervention was made (sham). In the IH group (n = 6), blood flow was lowered by stepwise hemorrhage; in the HH group (n = 6), hydrochloric acid was instilled intratracheally. We measured cardiac output, superior mesenteric blood flow, gases, hemoglobin, and oxygen saturations in arterial blood, mixed venous blood, and mesenteric venous blood, and ileal intramucosal PCO2 by tonometry. Systemic and intestinal oxygen transport and consumption were calculated, as was ΔPCO2. After basal measurements, measurements were repeated at 30, 60, and 90 minutes. Results. Both progressive bleeding and hydrochloric acid aspiration provoked critical reductions in systemic and intestinal oxygen delivery and consumption. No changes occurred in the sham group. ΔPCO2 increased in the IH group (12 ± 10 [mean ± SD] versus 40 ± 13 mmHg; P < 0.001), but remained unchanged in HH and in the sham group (13 ± 6 versus 10 ± 13 mmHg and 8 ± 5 versus 9 ± 6 mmHg; not significant). Discussion. In this experimental model of hypoxic hypoxia with preserved blood flow, ΔPCO2 was not modified during dependence of oxygen uptake on oxygen transport. These results suggest that ΔPCO2 might be determined primarily by blood flow.